A Broadband Reflectarray Based on Vivaldi Antenna Elements - Fan Qin; Lihong Li; Yi Liu; Hailin Zhang (Applied Computational Electromagnetics Society Journal (ACES), 2020)
In this paper, a novel broadband reflectarray (RA) is presented. For achieving broadband performance, the unit cell is realized using Vivaldi antenna element, where the feeding line acts as phase delay-line for adjusting the reflection phase. By simply changing the length of phase delay-line, a full 360° phase coverage is obtained. Additionally, the phase response curves are nearly parallel within a broad bandwidth, leading to a wideband operation. To verify this design, a prototype consisting of 10×22 unit cells is designed, fabricated and measured. The measured results show that the maximum gain reaches 21.50 dBi with 20.15% 1-dB gain bandwidth and 30.38% 3-dB gain bandwidth, respectively. Simulated and measured results agree very well with the proposed design scheme.